The Dedication of Notarial Profession in Providing Legal Services to the Community of Tenjo Village, Tangerang Regency - Dewi Tjandraningsih (The International Journal of Education Management and Sociology, 2025)
The notary profession plays a vital role in ensuring legal certainty and protection for the public, including those in rural areas such as Tenjo Village, Tangerang Regency. This study aims to examine the form of dedication and concrete contributions of notaries in serving rural communities in legal matters, particularly in the drafting of authentic deeds, legal counseling, and assistance in civil legal issues. Using a descriptive qualitative approach and field observation, the research reveals that notaries are essential in addressing the low level of legal awareness among villagers, especially concerning land rights, inheritance, and private agreements. The notary's dedication is evident through direct outreach, proactive legal education, and bridging the gap between public legal needs and the formal legal-administrative system. The findings show that the notary’s presence in village settings represents more than professional obligations it embodies social commitment that strengthens legal awareness and compliance within the local community.